Clinical Features of the Ophthalmic Status in Pregnant Women - V. N. Trubilin; E. G. Poluninа; D. V. Andzhelova; E. E. Kazaryan; Yu. V. Evstigneeva (Oftalʹmologiâ)
Ophthalmologist consultation has an important role in the examination of pregnant women. In some cases, his conclusion can play a decisive role in choice of delivery method. Obstetricians-gynecologists rely on ophthalmologist opinion for determining the severity of preeclampsia; it affects the treatment tactics and the life of mother and child. Examination of a pregnant woman has a number of characteristics, with regard to them, 3 groups of patients, which can be identified: the first group — Physiological pregnancywithout ophthalmological pathology. The second group: Physiological pregnancy with eye pathology in the anamnesis: myopia, peripheral choriovitreoretinal dystrophy; retinal detachment, vitreous body, vascular membrane, etc. Third group — Pathologically flowing pregnancy with pathology resulting from pregnancy: pre-eclampsia, anemia, diabetes and others pregnant. In physiological pregnancy without ophthalmological pathology, the most common physiological changes are increased pigmentation around the eyes, ptosis, a decrease of conjunctival capillaries, changes of cornea sensitivity and thickness, and, consequently, a change in refraction with a myopic shift, a decrease of tolerance to contact lenses, a decrease intraocular pressure, hemeralopia. It is necessary to differentiate the physiological feature of pregnancy, which include, in particular, the shift of refraction to the myopia, from pathological manifestations such as retinal angiopathy, macular edema, central serous chorioretinopathy and others. An important aspect is the  identification of potentially dangerous conditions of laser retina coagulation no later than 34 weeks of gestation with considering thepossibility of rheumatogenic retinal detachment and dystrophic changes in the delivery. This procedure can allow avoiding operativedelivery in the second group of patients. Timely detection of angiospasm on fundus in patients with pre-eclampsia from the third group, will make the right choice in the tactics of managing a pregnant woman. Carrying out the minimum instillation medication regime, especially in the first trimester of pregnancy, will make it possible to reduce the negative impact of therapy on the mother and child